1993
DOI: 10.2135/cropsci1993.0011183x003300040026x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Injury during Early Floral Bud Development in Cowpea

Abstract: Heat stress during the vegetative and early reproductive stages induces floral bud abortion in cowpea [Vigna unguiculata (L.) Walp.] and several other crop species growing under long days, and can substantially reduce productivity. The objective of this study was to determine whether there is a specific developmental stage when heat stress causes abortion of floral buds. Cowpea plants were grown in four reach‐in growth chambers under either metal halide‐based (MH) or fluorescent‐based (FL) lighting systems wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…However, only a few studies have been conducted so far regarding the mechanism of FBA, and most of these studies have only focused on the effects of exogenous hormones and environmental stress on FBA (Ahmed and Hall, 1993;Bosac et al, 1994;Mouhouche et al, 1998;Krupnick et al, 2000;Warner and Erwin, 2005). Only a few studies have investigated FBA at the molecular level, such as gene expression patterns (Jia and Zhang, 2008;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a few studies have been conducted so far regarding the mechanism of FBA, and most of these studies have only focused on the effects of exogenous hormones and environmental stress on FBA (Ahmed and Hall, 1993;Bosac et al, 1994;Mouhouche et al, 1998;Krupnick et al, 2000;Warner and Erwin, 2005). Only a few studies have investigated FBA at the molecular level, such as gene expression patterns (Jia and Zhang, 2008;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…FBA is a widespread phenomenon in plant reproduction and evolution, having been observed in Cucurbita texana (Krupnick et al, 2000), dwarf bean (Mouhouche et al, 1998), cowpea (Ahmed and Hall, 1993), rape (Bosac et al, 1994), Chinese cabbage (Zhang et al, 2010), radish (Liu et al, 2008;Jia and Zhang, 2008), and the model plant Arabidopsis thaliana (Warner and Erwin, 2005). FBA is most commonly thought to result from abiotic stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warrag & Hall (1984) reported that HNT induced male sterility and excessive floral abscissions in cowpea, whereas high day temperature had no adverse effect. The HNT can decrease crop yields by decreasing crop growth duration, suppressing floral bud development and decreasing pollen production and viability (Ahmed & Hall, 1993;Mohammed & Tarpley, 2009a;Prasad et al, 1999;Prasad et al, 2006). Increase in NT from 27 o C to 32 o C decreased crop growth duration by 2 days, as indicated by emergence of 1 st panicle, in rice (Fig.…”
Section: Effects Of High Night Temperature On Yield and Yield-relatedmentioning
confidence: 96%
“…Suppression of floral buds under long days occurred under hot nights but was greater under the combination of hot nights and very hot days (Dow El-Madina and ). Transfer and heat-pulse experiments demonstrated that plants did not have a particular stage of development where they were very sensitive to high night temperature but that the duration of heat experience may be critical for the suppression of floral bud development (Ahmed and Hall 1993). Two weeks or more of consecutive or interrupted hot nights during the first four weeks after germination caused complete suppression of the development of the first five floral buds on the main stem (Ahmed and Hall 1993).…”
Section: Heat Stress Effects In Subtropical Zonesmentioning
confidence: 99%